Maintaining stability of the rumen ecosystem is associated with changes of microbial composition and epithelial TLR signaling. Issue 3 (21st January 2017) - Shen, Hong; Chen, Zhan; Shen, Zanming; Lu, Zhongyan
Abstract: We used the goat as a model to study the effects of rumen microbial composition and epithelial TLR signaling on maintaining rumen stability during exogenous butyrate interference. Six cannulated goats received a rapid intraruminal infusion of 0.1 mol/L potassium phosphate buffer with (BT, n  = 3) or without (CO, n  = 3) 0.3 g/kg·BW·day sodium butyrate for 28 days. The ruminal pH and the concentration of total SCFA were not affected by the interference. 16S rRNA gene amplicon sequencing revealed a change in microbial composition after the butyrate infusion. LEfSe analysis showed a shift of the biomarker species from butyrate‐producing bacteria to acetate‐and propionate‐producing bacteria. Quantitative PCR‐based comparisons showed that significant increases in TLR2, TLR5, and MyD88 expression were accompanied by a significant decrease in IL‐1β and IFN‐γ expression in the ruminal epithelium. Constrained correlation analysis showed that the relative abundance of Roseburia was positively correlated with the expression of TLR5. Taken together, our study shows that microbial composition plays an important role in maintaining the stability of the microbial ecosystem in rumen, and indicates that the microbe‐TLR‐cytokine axis was involved in maintaining the stability of the gastrointestinal ecosystem. Abstract : Our study shows that microbial composition plays an important role in maintaining the stability of the microbial ecosystem in rumen. The role of microbial composition is mediated by microbe‐TLR‐cytokine axis.